Kingdom. 6 - Hara, Yasuhisa, 1975- (Viz signature., 2026)
"Xin is a war orphan in a poor village in the kingdom of Qin. He has big dreams of becoming the Greatest General Under the Heavens, and when his best friend's life is cut short by political machinations, Xin finds himself on a quest to do what no one has ever done before--unify China. Xin and his small five-man unit of Qin infantry soldiers are finally in the thick of battle. Death surrounds these lowest-ranked fighters who are being used as cannon fodder against the kingdom of Wei's heavily armed soldiers. Things go from dangerous to terrifying, however, when the kingdom of Wei's infamous war chariots bear down on them. But staying true to his dreams, Xin refuses to back down, even if the rest of his unit is too scared...except for one very quiet and mysterious member of his unit--Qiang Lei." -- Back cover.